APPLICATION OF PIEZOELECTRIC MATERIAL FILM PVDF (Polyvinylidene Flouride) AS LIQUID VISCOSITY SENSOR - Julius, Hananto F. S, Santoso D.R. (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2011)
The use of piezoelectric materials in sensors and transducers are growing rapidly. This material can be applied in many ways. One of Piezoelectric material founded in market was sheet- shaped called PVDF film. PVDF film applications in sensors allow the use in many application. In this study, PVDF film is used as the liquid viscosity sensor using the principle of concentric cylinders. This research aims to design a sensor with a mechanical sensor that can be used for viscosity. In this study, the mechanical and electrical parts of the sensor was designed so that it can be used as a viscosity sensor. The design begins with designing the mechanical sensor consisting of a cylinder with diameter of 3 cm which at the upper end of the shaft mounted a circular plate as a place to attach the PVDF film sensor. This cylinder will be immersed in the outer cylider of 5 cm in diameter filled with test fluid. This outer tube is rotated so that the liquid then follow to spin, the test fluid spin will be rubbing against the cylinder resulting a force and torque on the cylinder. This force will be forwarded to the shaft and up to the plate that has been attached PVDF film. Due to this force, the PVDF electrode charge will arise. This charge by a charge amplifier is converted into a voltage proportional to the force felt by the inner cylinder. Viscosity will affect the force that drive PVDF film so that by measuring the output voltage will obtain the viscosity of the test fluid.Research was done by taking 10 samples of oil and 3 different size ofPVDF film and a strain gage,that are: 1 cm x 3 cm (PVDF1); 1 cm x 2 cm (PVDF2); 1 cm x 1 cm (PVDF3). Results showed that the resolution of PVDF1, PVDF2 and PVDF3 are 4.6 mv/cPois; 3.1 mv/cPois and 1.5 mv/cPois respectively, while the strain gage produce a resolution of 1.2 mv/cPois. The average resolution of PVDF is 1.53 mv.cPois-1.cm-2, which means that every 1 cm2 PVDF film area and the increase of 1 cPois of viscosity of the material will produce 1.53 millivolts.